Perlindungan Hukum Orang Dengan Gangguan Jiwa (ODGJ) Sebagai Korban Berdasarkan Undang-Undang Nomor 18 Tahun 2014 - Vivi Sylvia Purborini; Sarwo Waskito (Institute of Advanced Knowledge and Science, 2024)
Crime is an act that is contrary to applicable laws. In Indonesia, there are still many weaknesses in legal protection for people with mental disorders, the offenses used by public prosecutors still use the Criminal Code as in Article 285 including monitoring of legal resources. Until now, the means and efforts to provide legal protection for the status, rights, obligations, and roles of people with mental disorders have been carried out through various laws and regulations. The study discusses the rights of people with mental disorders and the Law in Indonesia and discusses the legal provisions in Law No. 18 of 2014. The type of research used is doctrinal (normative) research. It is explained that people with mental disorders are also protected by law to obtain care and a decent life according to their human dignity. The fulfillment of rights that are relatively running is the fulfillment of the right to medical assistance and rehabilitation carried out by the Witness and Victim Protection Agency. A number of fulfillments of victims' rights are also carried out on a limited basis by local governments. The restoration of victims' rights is based on the concept of a rights-based approach (human right-based approach). The human rights-based approach is a conceptual framework used for the process of human development. People with mental disorders who are victims of rape have the right to justice, that victims have the opportunity to seek justice. The perpetrators must be able to be prosecuted and brought to court and the victims must receive recovery and compensation.